Baseflow Index Analysis for Bengawan Solo River, Indonesia - Muh Taufik; Siti Annisa' (Agromet, 2022)
Hydrological investigation for major Java rivers remains research challenge todays, particularly in identification of runoff characteristics situated in monsoonal climate. This study aims to investigate the value of baseflow index for Bengawan Solo river. We employed daily streamflow data for period 1980-2010 to derive baseflow index (BFI) based on the smoothed minima. We utilized different approaches comprising the non-overlapping 3 days (BFI3), 5 days (BFI5), and 7 days (BFI7) of streamflow to compute the index. We found the average BFI3, BFI5, and BFI7 for this study period are 0.67, 0.56, and 0.49, respectively. It revealed that higher number of non-overlapping days would produce lower BFI, which could be an indication of less baseflow contribution to total streamflow. Additionally, our findings show there is an increasing trend of BFI in the last decade that may be associated with decreasing forest cover in the catchment area. Furthermore, the BFI value will provide a valuable information for key leader in water sector in particular during dry season, and further research is needed to integrate this BFI into sustainable water management index.